Analysis of Tendencies for Guessing Answers in Physics Objective Test - Risnawati Uding; Hartono Hartono; Ellianawati Ellianawati (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Nahdlatul Wathan Mataram, 2025)
This study aims to analyze students' tendency to guess answers on physics objective tests and how to guess based on gender, ability grouping, and grade level. The population of this study is all students of State Senior High School 31 Maluku and State Islamic Senior High School 4 Maluku. Quantitative data analysis in the form of physics semester test results was collected and analyzed with the Rasch Model using the Winstep Application, while qualitative data analysis was in the form of questionnaires and interviews. Students identified as guessing using RaschModel were 27 students, and 72 students were identified through interviews. The results of women's guesses were 68% correct, compared to men, who were only 32%. Students in high-ability groupings had a percentage of 77% correct guesses and 94% incorrect guesses from medium- and low-ability groupings. The way to guess students in high-ability groupings is by choosing the option with the smallest number, seeing the same numbers between the question and answer choices, and using mathematical operations